KLAIM PENGUASAAN SUMBERDAYA HUTAN DAMAR PADA PERSPEKTIF MASYARAKAT ADAT (LOKAL) DI AREAL PERTAMBANGAN (Kasus Masyarakat Desa Lalomerui Kecamatan Routa) - ., ISKANDAR (Buletin Penelitian Sosek, 2013)
The study objective was to determine the distribution in the area of ââ Damar Â in the concession area. PT. Rio Tinto, and how the ownership and control of Damar Â on the perspective of the community (local rule) and the government (state). Data collection techniques, interviews, participatory observation and FGDs (focus Grouf disscusion. Qualitative data analysis approach based on a research study issues described in the narrative. The results to found that the distribution of Damar in the village location Lalomerui divided into 13 locations in the Matamehu, Matamehu, Tawe, Mupute, Matarombeo, EMEA, Tabininda, Dambata, Tinangalewe, Lalobalo, Lamewua, Lalonbae and Watupali. This location is in the area around the mining project. Rio Tinto and the resin of some locations are in the project. resin ownership by the community as use rights, obtained by inheritance from parents and open a new location that had not been processed. In general, the limit control resin bounded by rivers, mountains and valleys, in addition to the topographic information is also known to be a possession limit of fellow Damar processing. Â Key words : Damar, Ownership, Use Rights, Local Rule